Investigating the Impact: Financial Literacy, Socio-Economic Status, and Awareness on Investment Decisions with Moderation Factors - Dewi Pertiwi; Adhityawati Kusumawardhani; James Tan Kristiyanto Pratama; Teripena Ika Sampurna Paul (Petra International Journal of Business Studies, 2024)
Investment decisions must be made appropriately so that investors are not trapped by investment scams.  But in fact, cases of investment scams are increasingly rampant in Indonesia.  The primary objective of this paper is to highlight the lack of financial literacy as one of the elements that might be responsible for Indonesia's substantial number of investment scam victims. To investigate the association between financial literacy, SES, awareness, and investment decisions, the model put out in this research employs logistic regression analysis. The results show that financial literacy has an impact on investment decisions, while SES has no influence on investment decisions. Awareness of fraudulent investments can moderate the relationship between financial literacy and investment decisions but cannot moderate SES on investment decisions. This study exhorts investors to base their investment choices on their financial literacy rather than on outside influences. Financial literacy training programs should be developed by the government, financial institutions, and educational institutions.